2020
DOI: 10.1051/aacus/2020016
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the influence of seating area design and enclosure on the seat-dip effect using scale model measurements

Abstract: The low-frequency attenuation in the direct sound due to the concert hall seats, i.e., the seat-dip effect, is studied with the help of a scale model comprising an adjustable seating area and an enclosed box. More particularly, different seat underpass sizes and floor raking angles are studied, and the results are averaged over multiple source positions. With the measurements on the seating area only, the main seat-dip frequency is found to depend on the seat back rest height, and on the degree of obstruction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Davies and Cox [12] compared the SDE attenuation with different seat absorptions and seat underpass shapes using the BEM simulation and a scale model and reported that changing the seat absorption had an audible influence on reducing the SDE in concert halls. Tahvanainen et al [18] conducted scale-model experiments to study the effect of the seat underpass and floor inclination on the SDE, and found that the dip frequency depended on the seat back height and on the obstruction degree of the seat underpass. However, little investigation and discussion on the possible mechanism was conducted in [12,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Davies and Cox [12] compared the SDE attenuation with different seat absorptions and seat underpass shapes using the BEM simulation and a scale model and reported that changing the seat absorption had an audible influence on reducing the SDE in concert halls. Tahvanainen et al [18] conducted scale-model experiments to study the effect of the seat underpass and floor inclination on the SDE, and found that the dip frequency depended on the seat back height and on the obstruction degree of the seat underpass. However, little investigation and discussion on the possible mechanism was conducted in [12,18].…”
Section: Introductionmentioning
confidence: 99%
“…Tahvanainen et al [18] conducted scale-model experiments to study the effect of the seat underpass and floor inclination on the SDE, and found that the dip frequency depended on the seat back height and on the obstruction degree of the seat underpass. However, little investigation and discussion on the possible mechanism was conducted in [12,18]. Takahashi [7] investigated the SDE phenomena via scale model measurements and derived a simple analytical model for attempting to explain the SDE mechanism.…”
Section: Introductionmentioning
confidence: 99%